Professional Burnout in The Concept of Sustainable Development of The Company - Izabela SZTANGRET (Communications of International Proceedings, 2022)
The concept of sustainable development of the company nowadays comprises the new phenomenon of professional burnout, which so far has been poorly recognized and scarcely considered in the activities of the company. Burnout syndrome is a complex of symptoms of a physical and emotional nature, resulting from various loads, including professional ones, and most often caused by stress. This problem mainly affects employees of companies whose operation consists in intensive interpersonal contacts with cooperators, clients and other stakeholders. Increasing awareness of the problem should and already results in preventive actions and a reaction to the existing burnout syndrome. Such a solution to the growing problem is seen in a number of activities related to well-being, included in the holistically approached concept of sustainable development. The purpose of the paper is to define the basic research categories of the subject of the study, to define the structure of the contemporary model of the concept of sustainable development and the methods of its implementation. The research is exploratory in nature, it includes methods of quantitative and qualitative analysis for the purpose of discussing the results of secondary research. The conducted primary research is only a pilot study, preceding in-depth explanatory research planned for the near future.
Keywords: balanced development; model of balanced development; professional burning out; well-being; sustainable development